Understanding the shift from permanent employment to contract work among retail workers who accepted voluntary retrenchment packages in 2017 - Andrews, Lorenzo Daniel (Department of Sociology, 2022)
Cost saving strategies gained prominence in South Africa's retail sector when the Multinational Corporation (MNC) Walmart entered South African retail industry through the Walmart/Massmart Merger in 2011. Retail companies such as Pick n Pay (PnP) adopted workplace-restructuring strategies to maintain a competitive edge in the retail sector. This study draws attention to the effect of the cost saving strategies such as VRPs, and labour brokers in the workplace. This research explores the experience of retail workers who took voluntary retrenchment package (VRP) in 2017 and then returned to the same workplace as contract workers through labour brokers. This study specifically focuses on the experience of the transition from being a permanent worker with access to various employment benefits to a contract worker without access to typical benefits associated with industrial citizenship. The study adopted a qualitative research design with 10 semi-structured interviews. Using the worlds of work model and the concept industrial citizenship for analysis, this study finds that workplace restructuring strategies have led to the erosion of workers' industrial citizenship rights and has given rise to high levels of precarious working conditions. This illustrates that despite access to information sessions organised by PnP, workers were not adequately prepared for post-work life especially where finances were concerned. Due to their age, limited skills set for jobs outside the retail sector which affected their employability and the fact that they could not maintain their household needs after taking the VRP, workers returned to the same workplace as contract workers. This study finds that workers had a negative experience when they returned to their former workplace as casual workers because employment through labour brokers takes the employment accountability away from the company even though the worker is physically working under the PnP brand. Due to their long service at PnP, workers experienced the transition from being a permanent to contract worker in two ways. Firstly, by noting the erosion of industrial citizenship rights in their workplace. For example, workers experienced precarious conditions such as unfair dismissal, irregular and long working hours, less wages and received no employment benefits nor trade union representation. Secondly, by noting that there was a major shift from the traditional family-owned management style that made them feel like they were part of a family in previous years, to a corporate business set up that made them feel marginalized and unrepresented by trade unions.